Reflective Training and Its Impact on Developing Professional Competencies of Pre-Service Teachers in Morocco’s Regional Centres for Education and Training Professions - Agouzoul, El Mehdi; El Hammouchi, Abdelaziz; Faik, Toufik (Journal of Pedagogy and Education Science, 2025)
This study examines the pedagogical design of the Regional Centres for Education and Training Professions (RCETP), focusing on three training dimensions: functional knowledge, professional competence, and reflective practice. In this study, particular attention is devoted to the reflective dimension because it provides an essential entry point for addressing conceptual and methodological challenges in pre-service teacher educational training. This research adopts a qualitative approach based on participatory observation of training sessions and activities within selected RCETP programs in different regional centres in Morocco. This method offers direct insight into the daily dynamics of teacher preparation and the ways reflective practice is woven into training processes. Drawing on a competency-based framework, the analysis explores how training modules encourage trainee teachers to develop reflective professional skills that move beyond routine classroom practice. These skills enable future teachers to examine their teaching critically, conduct interventional educational research, and design context-sensitive pedagogical materials and resources. Findings indicate that integrating the reflective dimension within training modules strengthens the relationship between theoretical knowledge and practical application. It fosters critical thinking, professional autonomy, and the ability to generate innovative solutions to classroom challenges. The study concludes that prioritizing reflective practice enhances the holistic development of teacher professionalism and supports the continuous improvement of pre-service teacher education in Morocco.